The Characteristics Study of Palm oil-in-water Emulsion by Adding Gelatine as an Emulsifier Agent - RAPHAEL, SULIANA; Zakaria, Hanis (Research Progress in Mechanical and Manufacturing Engineering, 2023)
Abrasive blasting is a cleaning process for removal old paint coatings, corrosion and residues from metal surfaces. Water is used as a medium in the process of wet abrasive blasting represent new alternative to reduce fine dust released into the environment and potentially produce the formation of corrosion on the metal surface. However, until now there is still no solid evidence to determine that the palm oil-in-water emulsion has been applied into the application of blasting through their characteristic and psychochemical properties. This study will analyse the concept of oil-in-water palm emulsion to determine their characteristics and physicochemical properties when adding an emulsifier agent. RBD palm olein was selected and the emulsifying agent was used for the stability of oil-in-water palm emulsion. Emulsifying agents are used to facilitate the process of emulsification reduce the interfacial tension between oil and water due to hydrophilic and hydrophobic properties. The characteristic and physicochemical properties determine in this study are dynamic viscosity, density and creaming stability, microscopy image for visual analysis. The dynamic viscosity increases if the temperature decreases. The density of the emulsion also decreases as the speed missing process of the water and oil increases. In terms of creaming stability, the dynamic viscosity is higher when the use of more gelatine promotes the formation of cream on the surface of the resulting sample after a stirring. The results of the analysis for microscopy images size droplet of water and oil reduce when the speed of the mixing process is increased which results the remain stable. In conclusion, the use of gelatine as a natural emulsifier can increase the stability of the oil-in-water palm emulsion. The study recommend to use a relatively high stirring speed between 4000 rpm and above to achieve a viscosity reduction and enhance stability of emulsion